Dynamic viscosity and refractive index of aliphatic n-heptane with substituted aromatic hydrocarbons at T = (303.15 to 323.15) K and atmospheric pressure - M. Abdur Rahaman; M. Kamrul Hossain; Shamim Akhtar; Hossain M. Shahadat (Chemical Thermodynamics and Thermal Analysis)
Dynamic viscosity and refractive index of aliphatic n-heptane with substituted aromatic hydrocarbons, such as toluene, o-xylene, and mesitylene were measured at T = (303.15 to 323.15) K and atmospheric pressure. The measurements were carried out over the whole range of composition using A-type Ostwald viscometer and Abbe Utility (Abbe 60/E) refractometer. From dynamic viscosity data, viscosity deviation and excess Gibbs free energy of activation were calculated, while the excess molar refraction was obtained from refractive index data. The values of dynamic viscosity and refractive index were fitted with concentration dependent 4th order polynomial equation and their excess values to the Redlich–Kister type polynomial equation. The viscosity deviation and excess free energy of activation with respect to mole fraction of aromatic hydrocarbons formed negative lobe with minima at x2 = 0.55, whereas deviation of refractive index formed negative lobe for n-heptane + toluene system and positive lobe for n-heptane + o-xylene and n-heptane + mesitylene systems. Dispersive force is dominated in n-heptane + toluene system, whereas favorable geometric fitting is responsible for other two systems.